2015
DOI: 10.4314/jab.v92i1.3
|View full text |Cite
|
Sign up to set email alerts
|

Effets de l’hydrogel sur la survie et la croissance des plantules d’arganier sur une parcelle de régénération en climat aride.

Abstract: Defaa et al. J. Appl. Biosci.Effets de l'hydrogel sur la survie et la croissance des plantules d'arganier sur une parcelle de régénération en climat aride. 8586Effets de l'hydrogel sur la survie et la croissance des plantules d'arganier sur une parcelle de régénération en climat aride. RÉSUMÉObjectifs: L'objet de cette étude est l'évaluation à court terme de l'opportunité de réduction de l'eau d'arrosage en amendant le sol par un hydrogel ainsi que l'étude de ses effets sur le taux de survie et les paramètres … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
(16 reference statements)
2
3
0
Order By: Relevance
“…Under reduced irrigation frequencies, hydrogel amendment allowed for significantly improved growth in potting medium, clay- and sand-containing soils, leading to growth increased by 4%, 3% and 6% respectively, in comparison with non-amended conditions. These observations are in line with studies on Argania spinosa in arid region (C Defaa 2015), and on cucumber and basil plants in sandy soils (Montesano et al 2015).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Under reduced irrigation frequencies, hydrogel amendment allowed for significantly improved growth in potting medium, clay- and sand-containing soils, leading to growth increased by 4%, 3% and 6% respectively, in comparison with non-amended conditions. These observations are in line with studies on Argania spinosa in arid region (C Defaa 2015), and on cucumber and basil plants in sandy soils (Montesano et al 2015).…”
Section: Resultssupporting
confidence: 91%
“…On the other hand, the growths recorded with hydrogel supplementation were not significantly affected across conditions, except for clay-containing soils during limited watering. These observations are consistent with studies with Argania spinosa on arid region [22], and on cucumber and basil plants in sandy soils [11]. Under limited irrigation, hydrogel supplementation led to significantly improved growth in potting medium, sand- and clay-containing soils with heights of 108%, 101% and 107% their initial heights, respectively.…”
Section: Resultssupporting
confidence: 91%
“…According to Wang and Boogher [20], hydrogels absorb various amounts of water during expansion and have been found to increase water retention in potting media, thus reducing the irrigation frequency and delaying the onset of wilting. Adding hydrogel to soil demonstrated a positive impact on the development of argan seedling parameters [21], it significantly enhanced growth, root collar diameter and the slenderness index of plants. The biodegradable superabsorbent cellulose-based hydrogel used by Montesano et al [22] for sweet basil plants grown on perlite with hydrogel added showed an increase in fresh biomass.…”
Section: Resultsmentioning
confidence: 96%
“…In Morocco, hydrogels have been noted to have a highly significant effect on plant growth, contributing to remarkable height growth of argan plants from the fourth month after planting [12]. Additionally, Tyagi et al [13] and Hou et al [14] observed a stimulating hydrophilic superabsorbent effect on the yield of different crops, such as potatoes and maize, under various soil conditions According to Johnson [15], the use of hydrogels increases available moisture in the root zone, which implies longer intervals between irrigations.…”
Section: Introductionmentioning
confidence: 99%